Revision of the genus Zeugophora (Coleoptera, Megalopodidae, Zeugophorinae) in Japan - Takemoto, Takuya (Zootaxa, 2019)
Japanese species of the genus Zeugophora Kunze, 1818 (Coleoptera, Megalopodidae, Zeugophorinae) are revised. In this publication, Zeugophora annulata (Baly, 1873), Z. unifasciata (Jacoby, 1885), Z. hozumii Chûjô, 1953, Z. japonica Chûjô, 1951, Z. varipes (Jacoby, 1885), Z. chujoi Ohno, 1961, Z. flavonotata (Chûjô, 1935), and Z. gracilis unicolor Chûjô, 1958 are redescribed, with detailed illustrations of the male and female genitalia. Additionally, Z. nigricollis (Jacoby, 1885) is restored to a valid species from junior synonymy with Z. bicolor (Kraatz, 1879), and Z. cupka sp. nov., is described as a new species.